Vegetable Leafminer, Liriomyza sativae Blanchard (Insecta: Diptera: Agromyzidae) - John L. Capinera (EDIS)
This document is EENY-255, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: December 2001.